IMPLEMENTASI KEPEMIMPINAN ADAPTIF KEPALA SEKOLAH DI SEKOLAH DASAR - Indiarto, Arif; Kusnandi, Kusnandi; Sumiati, Sumiati; Rahman, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of adaptive leadership by principals in improving team performance and teacher professionalism in elementary schools. The research background is based on the importance of the principal's role as an educational leader who not only possesses technical competence but also adapts to the dynamics and challenges of the school environment. This study used a qualitative approach with stages of orientation, exploration, concept verification, and reliability analysis. Data were obtained through an in-depth study of principal leadership practices in a real-world context. The results indicate that adaptive leadership is manifested through three main aspects: diagnostic leadership, the creation of a comfortable and conducive work environment, and humanistic leadership. Diagnostic maintenance is carried out through observation and identification of comprehensive school conditions before policymaking. Creating a conducive work environment can improve team cohesion, motivation, and collaboration among teachers. Meanwhile, humanistic leadership, demonstrated through openness, appreciation, and emotional support, contributes to increased teacher motivation and professionalism. Thus, the adaptive leadership of principals has proven to be key to continuously improving the quality of education.